Magnitude of Episiotomy and Associated Factors among Mothers Who Give Birth in Arba Minch General Hospital, Southern Ethiopia: Observation-Based Cross-Sectional Study - Kassahun Fikadu; Negussie Boti; Birtukan Tadesse; Dureti Mesele; Emenet Aschenaki; Etenesh Toka; Fistum Arega; Tsehaynesh Girma; Abebech Paulos (Journal of Pregnancy)
Background. Episiotomy is the most common obstetric procedure, performed when the clinical circumstances place the patient at a high risk of high-degree laceration. However, episiotomy should be done with judicious indication to lower perineal laceration with fewer complications. Despite its adverse effects, the magnitude of episiotomy is increasing due to different factors. Therefore, this study is aimed at determining the recent magnitude of episiotomy and at identifying associated factors among women who gave delivery in Arba Minch General Hospital, Southern Ethiopia. Methods. An institution-based cross-sectional study was conducted from December 15, 2018, to January 30, 2019. A systematic random sampling technique was used to select study participants. A semistructured questionnaire was used to collect data. This was supplemented with a review of the labor and delivery records. Binary and multivariable logistic regression analyses were performed to identify factors associated with the magnitude of episiotomy. P value ≤ 0.05 was used to determine the level of statistically significant variables. Results. The magnitude of episiotomy was found to be 272 (68.0%) with 95%CI=64.0‐72.5. Women who attended secondary education [AOR=10.24, 95%CI=2.81‐37.34], women who attended college and above [AOR=4.61, 95%CI=1.27‐16.71], birth weight≥3000 g [AOR=4.84, 95%CI=2.66‐8.82], primipara [AOR=4.13, 95%CI=2.40‐7.12], being housewife occupants [AOR=3.43, 95%CI=1.20‐9.98], married women [AOR=2.86, 95%CI=1.40‐5.84], and body mass index<25 kg/m2 [AOR=2.85, 95%CI=1.50‐5.44] were independent variables found to have significant association with episiotomy. Conclusion. The magnitude of episiotomy was 68.0% which is higher than the recommended practice by WHO (10%). The study participants’ occupational status, marital status, educational status, parity, birth weight, and BMI were significantly associated with the magnitude of episiotomy in the study area. Therefore, to reduce the rate of episiotomy, it is better to have periodic training for birth attendants regarding the indication of episiotomy.